Collimated terahertz radiation through a laser irradiating on a T-type target - Lv, Chong; Sun, Wei; Ban, Xiaona; Wan, Feng; Wang, Zhao (Frontiers in Physics, 2022)
A novel scheme, applying a linearly polarized laser irradiating on a T-type target which contains a longitudinal target followed by a transverse target, is proposed to collimate the terahertz radiation. The results show that the interaction between the laser and the longitudinal target can effectively reduce the electron transverse divergence while increasing the electron maximum cut-off energy. In this way, the terahertz radiation can be well collimated while enhancing its intensity. By using two-dimensional particle-in-cell simulations, we show that the pointing angle is about -13.6° and 17.5° when the length and thickness of the longitudianl target is 90λ and thickness 4.0λ, respectively. In addition, the impact of the laser and target parameters on the collimation of terahertz radiation are also investigated separately. Such a scheme may pave a new way for enhancing and collimating the terahertz radiation via laser-solid interactions.